Combination of CD157 and FLAER to Detect Peripheral Blood Eosinophils by Multiparameter Flow Cytometry - Carulli, Giovanni; Marini, Alessandra; Sammuri, Paola; Domenichini, Cristiana; Ottaviano, Virginia; Pacini, Simone; Petrini, Mario (Journal of Clinical and Experimental Hematopathology, 2015)
The identification of eosinophils by flow cytometry is difficult because most of the surface antigens expressed by eosinophils are shared with neutrophils. Some methods have been proposed, generally based on differential light scatter properties, enhanced autofluorescence, lack of CD16 or selective positivity of CD52. Such methods, however, show several limitations. In the present study we report a novel method based on the analysis of glycosylphosphatidylinositol (GPI)-linked molecules. The combination of CD157 and FLAER was used, since FLAER recognizes all GPI-linked molecules, while CD157 is absent on the membrane of eosinophils and expressed by neutrophils. Peripheral blood samples from normal subjects and patients with variable percentages of eosinophils (n = 31), and without any evidence for circulating immature myeloid cells, were stained with the combination of FLAER-Alexa Fluor and CD157-PE. A FascCanto II cytometer was used. Granulocytes were gated after CD33 staining and eosinophils were identified as CD157-/FLAER+ events. Neutrophils were identified as CD157+/FLAER+ events. The percentages of eosinophils detected by this method showed a very significant correlation both with automated counting and with manual counting (r = 0.981 and 0.989, respectively). Sorting assays were carried out by a S3 Cell Sorter: cytospins obtained from CD157-/FLAER+ events consisted of 100% eosinophils, while samples from CD157+/FLAER+ events were represented only by neutrophils. In conclusion, this method shows high sensitivity and specificity in order to distinguish eosinophils from neutrophils by flow cytometry. However, since CD157 is gradually up-regulated throughout bone marrow myeloid maturation, our method cannot be applied to cases characterized by immature myeloid cells. [J Clin Exp Hematop 55(2) : 55-60, 2015]